The dynamics of regional and global expansion. Issue 4 (16th November 2015) - Asmussen, Christian Geisler; Nielsen, Bo Bernhard; Osegowitsch, Tom; Sammartino, Andre
Abstract : Purpose: – The purpose of this paper is to model and test the dynamics of home-regional and global penetration by multi-national enterprises (MNEs). Design/methodology/approach: – Drawing on international business (IB) theory, the authors model MNEs adjusting their home-regional and global market presence over time. The authors test the resulting hypotheses using sales data from a sample of 220 of the world's largest MNEs over the period 1995-2005. The authors focus specifically on the relationship between levels of market penetration inside and outside the home region and rates of change in each domain. Findings: – The authors demonstrate that MNEs do penetrate both home-regional and global markets, often simultaneously, and that penetration levels often oscillate within an MNE over time. The authors show firms' rates of regional and global expansion to be affected by their existing regional and global penetration, as well as their interplay. Finally, the authors identify differences in the steady states at which firms stabilize their penetration levels in the home-regional and the global space. The findings broadly confirm the MNE as an interdependent portfolio with important regional demarcations. Originality/value: – The authors identify complex interdependencies between home-regional and global penetration and growth, paving the way for further studies of the impact of regions on MNE expansion.